Penerapan Konvergensi dan Divergensi TV9 Lombok di Era Disrupsi - sahril halim; Anang Sujoko; Antoni Antoni (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2018)
Television broadcasting media continues to grow following the changing times and technology. The development of the media also has a major influence on the broadcasting industry so that it is possessed as a creative industry. In addition, the presence of an era of media media broadcasts to implement various strategies in the face of disruption. Similarly, TV9 Lombok as a broadcasting media must be more creative and innovative in the face of disruption. To answer the challenge of TV9 disruption Lombok implements convergence and divergence to be able to answer public problems that not only watch television conventionally but broadcasts public television broadcasts online content. Media convergence shows how to combine media on various platforms. While media divergence is a function that is needed in convergence as media that spreads widely while redistributing broadcast content as a whole. The concept of divergence and convergence is implemented as an effort of TV effectiveness in producing news content and broadcasting by utilizing streaming and social media to get closer to viewers so that TV9 Lombok broadcasts media and other fields such as waterpark TV9, Rural Banks ( BPR) and the Atamin Mineral Water Company. This was done by TV9 Lombok as an effort to maintain its existence in the world of broadcasting.